REASEARCH ON HIGH ENERGY DENSITY PULSE CURRENT REDUCTION RESIDUAL STRESS IN Cr12MoV STEEL QUENCHING SPECIMEN - WANG SiQi; GU BangPing; HU Xiong; XU GuanHua; WANG Ping; ZHUANG JiaYi; WU ChenYu (Jixie qiangdu)
Aiming at the problem of introducing large residual compressive stress on the surface of the material due to the quenching process,the high energy density electric current pulse（ECP） technology was introduced to reduce the residual stress in Cr12 MoV steel.The samples were treated with different density ECP and the residual stress and surface hardness of the materials before and after ECP were analyzed by the hole-drilling method and hardness test method.Based on this,an electroplastic model framework was established to explain the mechanism of ECP on residual stress and surface hardness.The results show that high energy density ECP can effectively eliminate the residual stress of quenched Cr12 MoV steel,and increasing the density of the ECP within a certain range can improve the residual stress reduction effect; Surface hardness of quenched Cr12 MoV steel decreased from 61 HRC～64 HRCto 56 HRC～59 HRC;The reduction in dislocation density is an essential cause of residual stress release and surface hardness reduction.The high energy density ECP can be used to reduce the residual stress caused by the quenching process and improve the service life of the parts,which has certain engineering application value.